Real-time monitoring through the use of technology to enhance performances throughout HIV cascades. Issue 5 (September 2017) - Avery, Matthew; Mills, Stephen J.; Stephan, Eric
Abstract : Purpose of review: Controlling the HIV epidemic requires strong linkages across a 'cascade' of prevention, testing, and treatment services. Information and communications technology (ICT) offers the potential to monitor and improve the performance of this HIV cascade in real time. We assessed recent (<18 months) peer-reviewed publications regarding uses of ICT to improve performance through expanded and targeted reach, improved clinical service delivery, and reduced loss to follow-up. Recent findings: Research on ICT has tended to focus on a specific 'silo' of the HIV cascade rather than on tracking individuals or program performance across the cascade. Numerous innovations have been described, including use of social media to expand reach and improve programmatic targeting; technology in healthcare settings to strengthen coordination, guide clinical decision-making and improve clinical interactions; and telephone-based follow-up to improve treatment retention and adherence. With exceptions, publications have tended to be descriptive rather than evaluative, and the evidence-base for the effectiveness of ICT-driven interventions remains mixed. Summary: There is widespread recognition of the potential for ICT to improve HIV cascade performance, but with significant challenges. Successful implementation of real-time cascade monitoring will depend upon stakeholder engagement, compatibility with existing workflows, appropriate resource allocation, and managing expectations.